Commentary on Plato's Republic,Volume 1, Essays 1-6 - Proclus Diadochus 412-485 (Cambridge University Press, 2018)
The commentary on Plato's Republic by Proclus (d. 485 CE), which takes the form of a series of essays, is the only sustained treatment of the dialogue to survive from antiquity. This three-volume edition presents the first complete English translation of Proclus' text, together with a general introduction that argues for the unity of Proclus' Commentary and orients the reader to the use that the Neoplatonists made of Plato's Republic in their educational program. Each volume is completed by a Greek word index and an English-Greek glossary that will help non-specialists to track the occurrence of key terms throughout the translated text. The first volume of the edition presents Proclus' essays on the point and purpose of Plato's dialogue, the arguments against Thrasymachus in Book I, the rules for correct poetic depictions of the divine, a series of problems about the status of poetry across all Plato's works, and finally an essay arguing for the fundamental agreement of Plato's philosophy with the divine wisdom of Homer which is, in Proclus' view, allegorically communicated through his poems